Penetration of Dissected Membrane for False Lumen Embolization in a Case of Chronic Aortic Dissection. (January 2022) - Ichihashi, Shigeo; Nagatomi, Satoru; Iwakoshi, Shinichi; Hirose, Tomoaki; Bolstad, Francesco; Kichikawa, Kimihiko
Background: Patent false lumens carry a high risk of aortic events including rupture. False lumen embolization is a useful method to promote thrombosis of false lumen. In the case presented here, direct penetration of the dissected membrane was employed to obtain access to the false lumen, enabling embolization.Case report: The case was a 64-year-old female who developed a Stanford type A acute aortic dissection. Replacement of ascending aorta and aortic arch with frozen elephant trunk technique was performed. After the operation, there was a residual flow through the false lumen in the descending thoracic and abdominal aorta. Twenty months later, the patient complained of sudden back pain, and a CT scan demonstrated another new dissection at the distal edge of the open stent. Additionally, the false lumen that had remained since the onset of the type A aortic dissection enlarged during the observation period. An endovascular procedure was planned to exclude the false lumen. Despite closing all communicating channels between true and false lumen using a vascular plug, coils, and stent grafts, the false lumen continued to expand due to the residual flow at the visceral segment. The origin responsible for the flow was not identified. To perform an embolization of the false lumen, access into the false lumen was obtained by penetration of the dissected flap using a trans-septal needle. Following the successful penetration of the flap, embolization of the false lumen was performed using coils and glue. After the embolization, an angiogram of the false lumen confirmed the significant reduction of leakage into the true lumen. The size of the aorta and false lumen decreased after the embolization.Conclusion: Direct penetration of the dissected membrane of the aorta was a safe and useful measure for regaining access to the false lumen and for the following endovascular intervention.